Canadians in the Manichean Universe of War: The Novels of Ralph Connor - Anna Branach-Kallas (Studies in 20th & 21st Century Literature, 2017)
The purpose of my article is an analysis of two war novels by Canadian best-selling author Charles W. Gordon, known to his readers under the pseudonym of Ralph Connor (1830-1937): The Major (1917) and The Sky Pilot in No Man’s Land (1919). At the age of fifty-four, Connor was sent to the front as a preacher; only a fourth of his battalion survived, which made his determined to support the cause of the Empire in North America. His sentimental romances were written to support the war effort (The Major) or consolidate the myth of Canada’s valorous sacrifice in the Great War (The Sky Pilot in No Man’s Land). In my interpretation, I intend to show how in The Major Connor uses Manichean dichotomies to oppose the Allies to German characters; as a result, the Great War is represented in this novel as a defence of Christianity and European civilization. Love relationships in the novel serve, additionally, to depict the binary opposition between the noble British and Canadian characters and the corrupted and aggressive German ones. Larry Gwynne, the hero of the novel, is a Quaker, opposed to violence and bloodshed, yet, in spite of his initial opposition to military conflict, he eventually supports the Sacred Cause. The Sky Pilot in No Man’s Land in turn depicts Canadians competing to send money, resources, and soldiers to Europe when the war is declared. Connor’s volunteers are only motivated by the desire to defend the Motherland - Britain; he fails to mention such factors as unemployment that, as we know today, had a huge impact on enlistment in Canada. The central protagonist, in spite of his physical weakness, joins the Canadian Corps at the front. In the portrait of Barry Dunbar, Connor refers to the concept of muscular Christianity, an ideal of physical and religious discipline, fusing honour, courage and manhood with a modernised conception of Christian love, responsibility and sacrifice, which was key to his earlier success. Barry is a charismatic preacher, who teaches the soldiers in his battalion to die peacefully for the sake of God and the Empire. Death in the war, represented as a sacred crusade, is the ultimate sacrifice Canadian soldiers, Christ-like, are eager to face, confident about the righteousness of the Holy Cause and their own immortality. In conclusion, I demonstrate, how, using nineteenth-century aesthetic models, Connor created the model of the Great War novel in Canada.
Keywords: Great War; Canada; Manichean; muscular Christianity; propaganda